Structure features and fracture mechanisms of hexagonal boron nitride based composite materials - Vishnyakov, L.R.; Mazna, A.V.; Sinaisky, B.M.; Vereschaka, V.M. (Functional Materials, 2007)
The structure and fracture mechanisms of hexagonal boron nitride based composite materials with formation of new phases (mullite and sialon) during hot pressing has been studied. The composite microstructure was found to be textured oriented due to morphology of crystal boron nitride particles and to be essentially independent of the composite phase composition. It has been shown that fracture mechanisms vary within the temperature range of 20 to 1500°C. The fracture within 20-1200°C range is brittle with boron nitride exfoliation in (001) planes. The composite strength at above 1200°C is defined by the onset of weakening of grain boundary phase and tough character of its fracture.